Antifungal Effect of Aloe Vera Extract on Otomycosis: A Review - Bimbi Angrayuni Delta (Eureka Herba Indonesia, 2022)
Otomycosis is a common disease that can cause a variety of complications, including involvement of the inner ear and, in rare cases, death. Otomycosis management can be difficult and requires close monitoring. There is currently no standardized treatment regimen for otomycosis, which opens up new treatment options such as the use of herbal medicine. Aloe barbadensis miller, also known as Aloe vera, is one of over 400 Aloe vera species and a member of the Liliaceae family. Several studies have shown that Aloe vera extract has antifungal properties. The purpose of this literature review is to identify the components of Aloe vera as well as the mechanism of action in the treatment of otomycosis. The articles chosen were all published in PubMed within the last six years. The review included 7 articles that were obtained.